ON THE ZEROS OF THE DERIVATIVES OF FIBONACCI AND LUCAS POLYNOMIALS - Nihal Yılmaz Özgür; Öznur Öztunç Kaymak (Journal of New Theory)
The purpose of this article is to derive some functions which map the zeros of Fibonacci polynomials to the zeros of Lucas polynomials. Also we find some equations which are satisfied by F 0 n (x) and so L 00 n (x). To obtain these equations, formulizations which are made up of hyperbolic functions for Fibonacci and Lucas polynomials are used.